Euphemism in News Elections Discourses in the Daily Jawa Pos - Hadiwijaya, Munawwir; Sunuyeko, Nurcholis; Mukarom, Mukarom (UIBU, 2024)
Newspapers these days tend to be less kind, especially when reporting on elections. Euphemisms can be used because journalistic discourse surrounding elections is essentially political. The purpose of this study is to describe the usage of euphemisms, including their form, meaning, and purpose. In this study, a qualitative descriptive method was employed. This research data is presented as words, phrases, and clauses found throughout the whole news discourse column concerning elections in the daily Jawa Pos issue from November 2023 for 12 discourses. The documentation approach was used to acquire data. The research findings demonstrate that euphemisms in simple words, phrases, and clauses are present in the news discourse regarding the election in the daily Jawa Pos for November. In news discussions around elections, euphemisms typically have meanings related to linguistic refinement and the concealment of unpleasant facts or events.